COMPARATIVE STUDY: THE DIFFERENCES STUDENTS’ LEARNING BASED ON GENDER - Natsir, Irmawaty; Munfarikhatin, Anis; Mayasari, Dian; Suryani, Dessy R.; Pagiling, Sadrack Luden (PATTIMURA UNIVERSITY, 2022)
This research is motivated by variuous ways in students absorb, organize and process information received, such as there are students easier to remember the material given visually than auditory or vice, there are students who difficult to write, but good telling stories, there are students who easily disturbed by noise, there are students can't sit still for a long time and there are students prefer practical activities. This study is a comparative to determine differences in learning styles between male and female students at SMP Yapis Merauke. The research sample amounted to 80 students. Data was collected from a learning style questionnaire and analyzed descriptively and inferentially. Descriptive analysis shows dominant male students had auditory and dominant female students had a visual learning style. Inferential analysis with the Anova test showed a significant value of p=0,00 (p<0,05), which means a difference between the learning styles of males and females